Perbandingan Variasi Matriks Resin Epoxy Dan Resin Polyester Pada Komposit Carbon Fiber Terhadap Kekuatan Uji Impak Dengan Standar ASTM D6110 - Sahroni; Firman Yasa Utama (CV. SINAR HOWUHOWU, 2026)
The development of automotive technology has increased the need for lightweight materials with high mechanical strength and good impact resistance. Motorcycle fenders commonly use conventional plastic materials such as Polypropylene (PP) and Acrylonitrile Butadiene Styrene (ABS), which have relatively low impact resistance, approximately 0.0605 J/mm² for impact value and 2.42 Joules for impact energy. Therefore, alternative materials with better mechanical properties are required. Carbon fiber composites are considered a promising alternative due to their lightweight characteristics, high strength, and excellent resistance to impact loads. This study aims to analyze the effect of epoxy and polyester resin matrix variations on the impact strength of carbon fiber composites based on ASTM D6110 standards. This research employed an experimental method using the vacuum infusion fabrication technique. The research stages included preparation of tools and materials, mold preparation, arrangement of 15 layers of carbon fiber, resin infusion, curing process, specimen cutting, V-notch fabrication according to ASTM D6110, and Charpy impact testing. The resin matrix variations used were Eposchon 1011 A Epoxy Resin, AM-8927 Low Viscosity Epoxy Resin, Yukalac 157 BQTN-EX Series Polyester Resin, and Eterset 2728-PC Unsaturated Polyester Resin. The specimens were prepared with dimensions of 126 mm × 12.7 mm and thicknesses ranging from 3–12.7 mm according to ASTM D6110 standards. The results showed that resin type significantly affected the impact energy and impact value of carbon fiber composites. The AM-8927 Low Viscosity Epoxy Resin produced the highest average impact energy of 14.97 Joules and the highest impact value of 0.3000 J/mm². These values were considerably higher than those of conventional PP/ABS motorcycle fender materials. The findings indicate that carbon fiber composites with epoxy resin matrices have strong potential as alternative motorcycle fender materials with improved resistance to impact loading.